Pemanfaatan lahan suboptimal di Majalengka dalam peningkatan produktifitas kedelai melalui teknologi kultivar dan pupuk hayati: Utilization of suboptimal land in majalengka to increase soybean productivity through dive fertilizer technology - Sukmasari, Miftah Dieni; Wijaya, Acep Atma; Sidik, Amir (AGROMIX, 2022)
Introduction: Efforts to increase the production of breakthrough cultivation innovations that can increase the productivity of wetlands/rainy seasons that are environmentally friendly, among others, through the use of biological fertilizers. The purpose of this study was to analyze the application of adaptive cultivars and optimal biofertilizers to soybean cultivation on suboptimal land. This research will be conducted in the Experimental area of ​​Cicurug Village from February to May 2021. Methods: research uses experimental methods in the field. The environmental design used is factorial RAK (Randomized Block Design). The first factor is cultivar and the second factor is biological fertilizer, including: K1 = Grobogan, K2 = Anjasmoro and K3 = Deja 2, the second factor is Biological Fertilizer (P) which consists of 4 levels, namely: P0 = 0 g/kg, P1 = 50 g/kg, P2 = 100 g/kg and P3 = 150 g/kg. The research variables observed were the agronomic and physiological responses of plants. Results: The results showed that the application of cultivars had an effect on the growth of soybeans grown on suboptimal land. The Anjasmoro cultivar gives better yields than other cultivars. In the application of biological fertilizers, the dose weight of 150 kg/ha was able to provide the most seeds/plot compared to other doses. Conclusion: The application of biological fertilizers and cultivars can increase soybean productivity in suboptimal land.